How to Smash the Next Billion Mobile App Bugs? - Chandra, Ranveer; Karlsson, Börje F.; Lane, Nicholas D.; Liang, Chieh-Jan Mike; Nath, Suman; Padhye, Jitu; Sivalingam, Lenin Ravindranath; Zhao, Feng (ACM GetMobile: Mobile Computing and Communications, 2015)
With users increasingly dependent on their phones, tablets, and wearables, the mobile app ecosystem is more important today than ever before. Creating and distributing apps has never been more accessible. Even single developers can now reach global audiences. But mobile apps must cope with extremely varied and dynamic operating conditions due to factors like diverse device characteristics, wireless network heterogeneity, and varied user behavior. App developers and operators of app marketplaces both lack testing tools that can effectively account for such diversity and, as a result, app failures and performance bugs (like excessive energy consumption) are commonly found today. To address this challenge to mobile app development, we have developed key techniques for scalable automated mobile app testing within two prototype services – VanarSena and Caiipa. In this paper, we describe our vision for SMASH, a unified cloud-based mobile app testing service that combines the strengths of both previous systems to tackle the complexities presently faced by testers of mobile apps.